Analysis of Sales and Cash Receipt Accounting Information Systems To Improve Internal Control Over Revenue At PT. Indomarco Prismatama Sidoarjo Branch Office: Analisa Sistem Informasi Akuntansi Penjualan Dan Penerimaan Kas Untuk Meningkatkan Pengendalian Internal Atas Pendapatan Pada PT. Indomarco Prismatama Kantor Cabang Sidoarjo - Astutik, Yuli; Nurasik, Nurasik (Universitas Muhammadiyah Sidoarjo, 2021)
The accounting system for sales and cash receipts operated at PT Indomarco Prismatama is used to improve internal control over revenue at PT Indomarco Prismatama in Sidoarjo branch offices. This accounting system is carried out to minimize errors and fraud in the process of selling and receiving cash, because there are executors in the field who deliberately cheat in carrying out their duties, but there are also executors who make mistakes but they do not intentionally or have no intention. The error is due to a procedure that was not executed. Therefore, the existence of an accounting system will be able to support the performance of employees in carrying out their duties properly.